Thyroid hormone receptor beta-2 (TRβ2) overexpression modulates photoreceptor phenotype diversity in a ligand-dependent manner - Owusu Poku, Emmanuel; Fonte, Matthew R.; Jensen, Tyler J.; Inman, Sydney P.; Mackin, Robert D.; Stenkamp, Deborah L. (Frontiers in Cell and Developmental Biology, 2025)
BackgroundVertebrate color vision results from the specification of photoreceptor subtypes expressing distinct opsins. Thyroid hormone (TH) and its receptor TRβ2 are essential regulators of long-wavelength-sensitive (LWS) cone development, but their ligand-dependent roles in regulating cone subtype fate remain unclear.MethodsWe investigated how varying TH availability and TRβ2 overexpression impact cone photoreceptor diversity and opsin expression using a gain-of-function transgenic zebrafish line (crx:trβ2), which expresses TRβ2 in all photoreceptors, and manipulated TH levels through T3 supplementation or ablation of the thyroid gland. Samples were analyzed through a combination of hybridization chain reaction in situ hybridization, confocal microscopy, and quantitative RT-PCR.Resultswe found evidence consistent with the hypothesis that unliganded TRβ2 predominantly promotes lws2 expression, while liganded TRβ2 upregulates lws1, following a dose-dependent and temporally dynamic pattern. Overexpression of TRβ2 promoted co-expression of lws2 in non-LWS cones, suggesting possible photoreceptor transfating. TH supplementation amplified these effects and induced changes in numbers and morphologies of cone subtypes with no obvious evidence of cell death. We also identified spatially distinct expression of key TH regulatory genes (dio2, dio3b, mct8) in the retina and retinal pigment epithelium, which responded dynamically to manipulation of TH levels.ConclusionOur findings suggest that TRβ2 exerts differential effects on cone opsin expression depending on presence and quantity of ligand.